Lula Dean's little library of banned books : [large type] a novel - Miller, Kirsten, 1973- (Harper Large Print, an imprint of HarperCollins Publishers, 2024)
When Lula Dean, trying to rid public libraries of "pornographic" books, starts her own lending library in front of her home, Lindsay, the daughter of Lula's arch nemesis, sneaks in nightly, secretly filling it with banned books wrapped in "wholesome" dust jackets, changing the lives of those who borrow them in unexpected ways.